Integrating sensory-based activity modules to enhance tactile sensitivity in Braille learners: a comparative study / Nurinsyirah Najihah Izharruzzahir … [et al.] - Izharruzzahir, Nurinsyirah Najihah; Khairil Anuar, Khairina Iqlima Batrisyia; Mohd Idris, Fadzidah; Mohamad Jan, Nurhidaya; Mohd, Siti Munirah; Sajab, Mohd Shaiful; Kaco, Hatika (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
Visual impairment and blindness are significant global health issues that severely impact the lives of affected individuals and those around them. These individuals encounter unique challenges in their daily routines and learning processes, which sighted people do not experience. Despite these obstacles, visually impaired individuals rely heavily on their tactile and auditory senses to perceive and understand their surroundings. Tactile sensory input is especially beneficial in conveying environmental and visual information to those who are visually impaired or blind. Therefore, a sensory-based activity module was developed to improve tactile sensitivity in learning Braille. This module consisted of four game stations: rice play, sand play, playdough, and finger paint. The participants’ tactile sensitivity was tested on their index and middle fingers, which are primarily used in reading Braille, both before and after engaging with the games. Specifically, the right middle finger exhibited an enhancement of up to 83%, the right index finger showed a 60% improvement, the left middle finger demonstrated a 71% increase, and the left index finger displayed a remarkable improvement of 298%. During the analysis of the module's effectiveness, it was discovered that an overwhelming 94% of the participants expressed great interest and found it highly impactful and over 70% of the participants successfully followed the game instructions and indirectly developed soft skills at each station. Additionally, there was a notable improvement in finger sensitivity, as measured by the two-point discriminator test. This interactive and enjoyable game-based learning approach is ideal for both blind and sighted players. It offers visually impaired individuals a practical method for learning Braille, enhancing their tactile sensitivity, and making the learning process more engaging and effective. The sensory play module not only supports the educational needs of visually impaired learners but also fosters an inclusive environment for all players.